Dissociations between developmental dyslexias and attention deficits - Lukov, Limor; Friedmann, Naama; Shalev, Lilach; Khentov-Kraus, Lilach; Shalev, Nir; Lorber, Rakefet; Guggenheim, Revital (Frontiers in Psychology, 2015)
We examine whether attention deficits underlie developmental dyslexia, or certain types of dyslexia, by presenting double dissociations between the two. We took into account the existence of distinct types of dyslexia and of attention deficits, and focused on dyslexias that may be thought to have an attentional basis: letter position dyslexia (LPD), in which letters migrate within words, attentional dyslexia (AD), in which letters migrate between words, neglect dyslexia, in which letters on one side of the word are omitted or substituted, and surface dyslexia, in which words are read via the sublexical route. We tested 110 children and adults with developmental dyslexia and/or attention deficits, using extensive batteries of reading and attention.For each participant, the existence of dyslexia and the dyslexia type were tested using reading tests that included stimuli sensitive to the various dyslexia types. Attention deficit and its type was established through attention tasks assessing sustained, selective, orienting, and executive attention functioning. Using this procedure,we identified 55 participants who showed a double dissociation between reading and attention: 28 had dyslexia with normal attention and 27 had attention deficits with normal reading.Each dyslexia with suspected attentional basis dissociated from attention:21 individuals with LPD,13 AD,2 neglect dyslexia,and 12 surface dyslexia. Other dyslexia types(vowel dyslexia, phonological dyslexia, visual dyslexia) also dissociated from attention deficits.Examination of 55 additional individuals with both a specific dyslexia and a certain attention deficit found no attention function that was consistently linked with any dyslexia type.Specifically, LPD and AD dissociated from selective attention, neglect dyslexia dissociated from orienting, and surface dyslexia dissociated from sustained and executive attention. These results indicate that visuospatial attention deficits do not underlie these dyslexias.